BUDDHIST SNAKES LADDERS PORTABLE AS LEARNING MEDIA FOR BUDDHIST SUNDAY SCHOOL'S STUDENTS - Bayu Jati Pamungkas; Didhit Taruna Putra; Riska Ayu Lestari; Ahsanul Khair Asdar (LPPM Universitas Negeri Jakarta, 2022)
This study aimed to develop a game of snakes and ladders as a learning media through the 4-D Thiagarajan model (Define, Design, Development, and Disseminate). This study's data was collected using an interview guide and questionnaires. The data was analyzed using Aiken's V, Gregory, and descriptive statistics. Aiken's V analysis showed that all of the questions were valid. Gregory's analysis showed that the game's manual book had an excellent readability level with an interrater agreement index of 0.857. The test results showed that the games developed were practical and can be used as learning media.